2013
DOI: 10.3390/ijerph10062370
|View full text |Cite
|
Sign up to set email alerts
|

Public Place Smoke-Free Regulations, Secondhand Smoke Exposure and Related Beliefs, Awareness, Attitudes, and Practices among Chinese Urban Residents

Abstract: Objective: To evaluate the association between smoke-free regulations in public places and secondhand smoke exposure and related beliefs, awareness, attitudes, and behavior among urban residents in China. Methods: We selected one city (Hangzhou) as the intervention city and another (Jiaxing) as the comparison. A structured self-administered questionnaire was used for data collection, and implemented at two time points across a 20-month interval. Both unadjusted and adjusted logistic methods were considered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Studies have demonstrated an association between smoke-free regulations and change in beliefs, attitudes and behaviors among both the public and health care providers (Yang et al, 2013; Gonzalez, Sanders-Jackson, Glantz, 2014). For health care workers, smoke-free air policies may work to denormalize smoking and increase the salience of addressing tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated an association between smoke-free regulations and change in beliefs, attitudes and behaviors among both the public and health care providers (Yang et al, 2013; Gonzalez, Sanders-Jackson, Glantz, 2014). For health care workers, smoke-free air policies may work to denormalize smoking and increase the salience of addressing tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…47 Still, previous research has found self-reports of SHS exposure to be strongly correlated with other biological markers of SHS such as ambient nicotine measurements. 56,57 A second limitation was that certain studies lacked clarity in reporting results (eg, not explicitly stating if results were statistically significantly different pre-and post-ban 36,39,46 or relying on small figures to demonstrate differences 52 ). Half of the studies did not mention missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Only five of the studies that Callinan et al reviewed were included in the present review. 29,36,37,39,52 Of the studies included in this review but not in Callinan et al's, 10 were published after their final literature search was conducted in July 2009 20,35,40,[46][47][48][49][50][51]54 and one was published prior. 53 Overall, the Callinan et al 2 article found no effect of legislative bans on home smoking restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations